UTILIZATION OF MORINGA OLIEFERA LEAVES COAGULANT FOR LEACHATE TREATMENT : CASE STUDY OF PASURUHAN LANDFILL, MAGELANG REGENCY - Rizqa Puspitarini; Riva Ismawati; Adi Iriyanto (Jurnal Inovasi Teknik Kimia, 2024)
Waste has caused environmental problems, especially waste processing that is not yet optimal. Open dumping waste processing is still used in waste processing. Open dumping waste processing will produce leachate pollution. The research aims to test the quality of leachate by utilizing the natural coagulant of Moringa leaves to reduce the total dissolved solids (TDS) and conductivity of the leachate. The coagulant was made by macerating Moringa leaves using 70% ethanol and leaving it for 72 hours. Moringa leaf coagulant was contacted with leachate samples from the Pasuruhan Magelang landfill using variations in coagulant mass and contact time. Treatment with a coagulant mass of 1 gram and a contact time of 10 minutes was able to reduce leachate TDS levels by 1020 mg/L with an effectiveness of 55.98%. Treatment with a coagulant mass of 1 gram and a contact time of 15 minutes can reduce the leachate conductivity by 2333 cm/s with 79.38%. The use of natural coagulants from Moringa oliefera leaves can be used as an alternative treatment method for handling leachate. Keyword:: Leachate, Moringa Oliefera